THE INFLUENCE OF ENGINE SPEED ON THERMAL STRESSES OF THE PISTON - Piotr GUSTOF; Aleksander HORNIK; Piotr CZECH; Damian JĘDRUSIK (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
In the paper, numeric calculations relating to the influence of engine speed on thermal stresses of the piston in a turbocharged diesel engine in the initial phase of its work were carried out. The calculations were based on experimental studies and the data resulting from them. They were made using a geometrical model of the piston in a turbocharged diesel engine with a capacity of 2,300 cm3, with a direct fuel injection to the combustion chamber and a power rating of 85 kW. Modelling of the thermal stresses of the piston was carried out for the engine speed n=2,000 min-1 and n=4,250 min-1.